The Effect of Using Social Media on Students’ Interest in Learning English - Dea Tresna Amalia; Septi Gumiandari (Journal Corner of Education, Linguistics, and Literature, 2023)
EF Education First, in its English Proficiency Index, shows data on the low interest in learning English among Indonesian students. Learning English is considered difficult because the material is quite extensive and the reading material is quite difficult. The use of social media is one of the factors that influence students' interest in learning English. This article aims to determine the effect of using social media on interest in learning English. This study uses a literature review approach, namely collecting references, reviewing theories, and analyzing the object being studied. Data were reviewed from all articles or journals published within the last 5 years. The results of this study indicate that the use of information technology, especially social media, can bring positive value if students can use these facilities for more positive things, for example, to increase knowledge, as a means of communication and also as a means of promoting something. The positive impact of students when using social media is to make social media a learning tool, especially language learning. Social media has a positive effect when social media such as YouTube, Instagram, TikTok are used as learning media; for example, it is used in making videos which can improve pronunciation and can package interestingly learning English. Thus, students' interest in learning English will increase.